Pemberian Hidroterapi (Rendam Kaki Air Hangat) untuk Mengatasi Risiko Perfusi Serebral Tidak Efektif pada Pasien Hipertensi - Sari, Dita Indah Wulan; Wulandari, Tri Suraning (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Jenderal Achmad Yani Yogyakarta, 2024)
Background: Hypertension or high blood pressure is a medical condition that can lead to ineffective cerebral perfusion risk. One of the non-pharmacological therapies that can be used to address this issue is hydrotherapy (warm foot immersion). Previous studies have shown the effectiveness of hydrotherapy in lowering blood pressure in hypertensive patients. Objective: This study aimed to determine the effectiveness of hydrotherapy (warm foot immersion) in addressing ineffective cerebral perfusion risk in hypertensive patients. Methods: This was a qualitative study with a case study design involving two adult female patients with hypertension and ineffective cerebral perfusion risk. The nursing intervention provided was hydrotherapy (warm foot immersion) for 30 minutes with water temperature around 40°C for three consecutive days. Data were collected through participatory observation and interviews, and analyzed by comparing patient facts with theory. Results: The evaluation results showed a significant decrease in blood pressure in both patients after hydrotherapy. In the first patient, blood pressure decreased from 169/96 mmHg to 150/87 mmHg, while in the second patient, it decreased from 184/123 mmHg to 151/102 mmHg. The cerebral perfusion evaluation results also showed a gradual improvement from the first day to the third day, with indicators ranging from moderately decreased to increased. Conclusion: This case study demonstrated that hydrotherapy (warm foot immersion) is effective in lowering blood pressure and addressing ineffective cerebral perfusion risk in hypertensive patients. These findings are consistent with previous research and support the use of hydrotherapy as a non-pharmacological intervention for managing this nursing problem.